Peran Bumdes Sebagai Social Enterprise Dalam Mewujudkan Desa Tematik Pangan - Kresnawati, Kresnawati; Prasetya, Andwini; Hanila, Siti; Febriano, Randy Rio; Rahayu, Hesti Riski (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Animal feed and goat farm waste are among the challenges faced by the Air Lang Jaya Village-Owned Enterprise (BUMDes) in IV Suku Menanti Village, Sindang Dataran District, Rejang Lebong Regency. These BUMDes business units include agro-tourism and nature tourism. Exploring the potential and problems of BUMDes, starting with focus group discussions (FGDs), digital marketing training, animal feed fermentation training, and animal manure processing, are methods used to address these issues. This training is expected to have an impact on improving the welfare of livestock farmers and BUMDes income. Farmer groups can maximize goat livestock yields through more nutritious feed, and animal manure marketed through BUMDes will have an impact on the income of BUMDes and livestock farmers. This activity demonstrates the role of BUMDes in improving food security at the village level. BUMDes can also develop more mature business plans for the future.